2005
DOI: 10.1186/1471-230x-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma and the penetrance of HFEC282Y mutations: a cross sectional study

Abstract: Background: Although most patients with hereditary haemochromatosis have HFE C282Y mutations, the lifetime risk to HFE C282Y homozygotes of developing fatal diseases such as hepatocellular carcinoma is uncertain. We have carried out a cross-sectional study to determine the proportion of diagnosed hepatocellular carcinoma patients who are homozygous for the HFE C282Y mutation; and to estimate the penetrance of this genotype with respect to hepatocellular carcinoma in East Anglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
0
31
1
6
Order By: Relevance
“…The association between rs1800562 and HCC has been controversial. We collected nine eligible association studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008) (including 1102 HCC cases and 3766 controls) to do the metaanalysis. By using the genetic analysis method (Thakkinstian et al 2005), we found the recessive model was most applicable to this disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between rs1800562 and HCC has been controversial. We collected nine eligible association studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008) (including 1102 HCC cases and 3766 controls) to do the metaanalysis. By using the genetic analysis method (Thakkinstian et al 2005), we found the recessive model was most applicable to this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygosity for mutation (Cys282Tyr, G [ A, rs1800562) in the HFE gene is responsible for the majority of cases of typical phenotypic HH (Ellervik et al 2007). However, the relationship of this mutation and HCC was controversial among reported studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…However, a crosssectional study showed that progression to HCC among hemochromatotic patients is mostly variable from one population to another, depending mainly on exposure to environmental factors that synergize the current underlying gene mutation (Willis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among the six studies, four studies [8,10-12] reported a significant association between HCC and the C282Y polymorphism (ORs > 1.0, 95%CIs did not include 1.0). Because the frequency of the homozygous mutation of C282Y is very low, and a large proportion of C282Y homozygotes had been diagnosed with HH and received treatment, such as venesection before developing LC or HCC, the conclusion that YY homozygotes increased HCC risk may have little clinical value.…”
Section: Discussionmentioning
confidence: 99%